Detection of ‘Candidatus Phytoplasma’ and ‘Ca. Liberibacter solanacearum’ strains in Solanum betaceum in Ecuador - Gabriele Giaccaglia; Carmen Isabel Castillo Carrillo; Francesco Pacini; Assunta Bertaccini (Physiological and Molecular Plant Pathology, 2026)

Periconceptional ambient temperature and adult atherogenic lipid profile: A life-course study of acute coronary syndrome patients and matched controls - Antonio Meseguer-Hernández; José Manuel Andreu-Cayuelas; Francisco Buendía-Santiago; Lidia Martínez-Gascón; María Isabel Baños-Maturano; Jaime Merino-Romero; Irene González-Fernández; Claudia Alejandra Azcondo-San Segundo; Leticia Risco-Eres; María Belén Villamarín-Heredia; Alberto Fernández-Reina; Juan Antonio Castillo-Moreno (International Journal of Hygiene and Environmental Health, 2026)

The IPBES invasion-management framework supports informed decision-making for managing biological invasions - Chika Egawa; K. V. Sankaran; Andy W. Sheppard; Evangelina Schwindt; Llewellyn C. Foxcroft; Sonia Vanderhoeven; Lora Peacock; Maria L. Castillo; Rafael D. Zenni; Jana Müllerová; Ana Isabel González Martínez; John K. Bukombe; et al. (Biological Invasions, 2026)
The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) Thematic Assessment Report on Invasive Alien Species and Their Control presents a “conceptual diagram of management-invasion continuum”, introducing a versatile framework to support decision-making on the management of biological invasions. Drawing on an extensive synthesis of current knowledge, this IPBES invasion-management framework has been developed to broaden the scope of existing invasion curves—which primarily overlay generic management objectives onto a sigmoid curve depicting the expansion of the affected area over time—and to illustrate the applicability of the concept of effective management at different stages of the biological invasion process. To introduce the IPBES invasion-management framework to a wider audience, this paper explains the features of the framework and defines the invasion-stage-based management approaches and the potential outcomes envisaged therein. Reflecting the currently limited management options for biological invasions in marine and other connected-water systems, unlike in terrestrial and closed-water systems, the IPBES invasion-management framework clearly distinguishes between these two groups of systems. For each, it presents management approaches including three key factors that decision-makers should consider concurrently: management objectives, targets, and actions. This framework supports informed decision-making in the management of biological invasions in all ecosystems.

Bioactive molecules from Agave salmiana bagasse: Study of their antioxidant, prebiotic potential, and cytotoxicity - Isabel Márquez-Rangel; Mario Cruz; Héctor A. Ruiz; Rosa M. Rodríguez-Jasso; Araceli Loredo-Treviño; Guillermo Castillo-Olvera; Ruth Belmares (Food Research International, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Serum trace elements and expression of antioxidant-related genes in the detection of women with ER-positive breast cancer - Paula Argente del Castillo; Pere Miquel Morla-Barcelo; Toni Martinez-Bernabe; Sara Sánchez Asís; Jose Antonio Delgado Rodríguez; Mercedes Nadal-Serrano; Isabel Llompart Alabern; Pilar Roca; Octavi Cordoba; Jorge Sastre-Serra; Josep Miquel Bauça (Journal of Trace Elements in Medicine and Biology, 2025)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Short-chain fatty acids in the treatment of ulcerative colitis. Systematic review and meta-analysis - Víctor Serrano-Fernández; Juan Manuel Carmona-Torres; Ángel López-Fernández-Roldán; Matilde Isabel Castillo-Hermoso; Sergio Rodríguez-Cañamero; Rosa María Molina-Madueño; José Alberto Laredo-Aguilera (Inflammation Research, 2025)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Solar-assisted Advanced oxidation processes affect the antibiotic resistance traits of bacteria developed in wastewater-irrigated soils: Are they a friend, a foe, or just a traitor in our midst? - Amira Yagoubi; Jeremie Decker; Clara Ortegón Salas; Isabel del Castillo González; Aurelio Hernández Lehmann; Rakia Chouari; Stefanos Giannakis (Chemical Engineering Journal, 2025)

Leaf Gene Expression in Response to Boron Toxicity in Native Maize (Zea mays L.) Cultivars - Mirko J. Ortiz; José Delatorre-Herrera; Juan Pablo Rodriguez Calle; Gerzon Moreno; Javier Palacios; Camila Molina; Víctor Espinoza; Cristopher Low-Pfeng; José Delatorre-Castillo; Isabel Sepúlveda-Soto (Journal of Soil Science and Plant Nutrition, 2025)

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Evaluation of disodium carboxymethyl trithiocarbonate as a depressant reagent for chalcocite: An electrochemical approach - Arait Montoya; Ivan Reyes; Roel Cruz; Isabel Lázaro; Néstor Castillo-Magallanes; Rogelio Flores; Israel Rodríguez (Minerals Engineering, 2024)

From rust to robust disinfectants: How do iron oxides and inorganic oxidants synergize with UVA light towards bacterial inactivation? - Jialin Jia; Marco Minella; Isabel del Castillo González; Aurelio Hernández Lehmann; Dong Li; Nuno P.F. Gonçalves; Alessandra Bianco Prevot; Tao Lin; Stefanos Giannakis (Science of The Total Environment, 2024)

Why is HSO5− so effective against bacteria? Insights into the mechanisms of Escherichia coli disinfection by unactivated peroxymonosulfate - Na Tian; Luciana Carina Schmidt; María Jesús Abeledo Lameiro; María Inmaculada Polo-López; María Luisa Marín; Francisco Boscá; Isabel del Castillo González; Aurelio Hernández Lehmann; Stefanos Giannakis (Water Research, 2024)

Homogeneous vs. heterogeneous photo-Fenton elimination of antibiotic-resistant bacteria bearing intracellular or extracellular resistance: Do resistance mechanisms interfere with disinfection pathways? - Jeremie Decker; Truong-Thien Melvin Le; Jose Manuel Entenza; Isabel del Castillo Gonzalez; Aurelio Hernandez Lehmann; Cesar Pulgarin; Jorge Rodriguez-Chueca; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2024)

Aspergillosis in a colony of Humboldt penguins (Spheniscus humboldti) in a french zoological park: evaluation of environmental exposure - Tristan Bralet; Veronica Risco-Castillo; Isabel Valsecchi; Sylvie Laidebeure; Anaïs Sailler; Alexis Lécu; Françoise Botterel; Jacques Guillot; Pascal Arné; Grégory Jouvion (Veterinary Research Communications, 2024)

Distribution and behaviour of striped dolphins in the southwestern Mediterranean Sea based on whale-watching data - Rosa Canales-Cáceres; Francisco Gomariz-Castillo; Francisco Alonso-Sarría; Isabel Abel; Francisca Giménez-Casalduero (Regional Studies in Marine Science, 2023)

Epidemiological features of Leishmania infantum in dogs (Canis lupus familiaris) suggest a latent risk of visceral leishmaniasis in the metropolitan area of Bucaramanga, Santander, Eastern Colombia - Jeiczon Jaimes-Dueñez; Adriana Castillo-Castañeda; Ángela Jiménez-Leaño; Jonny E. Duque; Omar Cantillo-Barraza; Diana Isabel Cáceres-Rivera; Yurany Granada; Omar Triana-Chávez; Juan David Ramírez (Preventive Veterinary Medicine, 2023)

Evaluating the durability and performance of polyoxometalate-ionic liquid coatings on calcareous stones: Preventing biocolonisation in outdoor environments - Stéphanie Eyssautier-Chuine; Isabel Franco-Castillo; Archismita Misra; Julien Hubert; Nathalie Vaillant-Gaveau; Carsten Streb; Scott G. Mitchell (Science of The Total Environment, 2023)

Effect of marine heat waves on carbon metabolism, optical characterization, and bioavailability of dissolved organic carbon in coastal vegetated communities - Luis G. Egea; Rocío Jiménez‐Ramos; Cristina Romera‐Castillo; Isabel Casal‐Porras; Paula Bonet‐Melià; Alba Yamuza‐Magdaleno; Lucía Cerezo‐Sepúlveda; José L. Pérez‐Lloréns; Fernando G. Brun (Limnology and Oceanography, 2023)
Dissolved organic carbon (DOC) plays an essential role in the global marine carbon cycle, with coastal vegetated communities as important DOC producers. However, the ultimate fate of this DOC remains still largely unknown due to the lack of knowledge about its chemical composition and lability. Furthermore, global change could alter both DOC fluxes and its bioavailability, affecting the carbon sequestration capacity of coastal vegetated communities. This study explores, in two contrasting seasons (winter and summer), the effects of an in situ simulated marine heatwave on carbon metabolism and DOC fluxes produced by seagrass ( Cymodocea nodosa ) and macroalgae ( Caulerpa prolifera ) communities. In addition, the fluorescent characteristics and biodegradability of the dissolved organic matter released directly by the communities under such conditions are evaluated. Under marine heatwave conditions, a significant increase in net community production (NCP) in C. nodosa and a shift to negative DOC fluxes in C. prolifera were observed. In control treatments, the seagrass‐dominated community produced a substantial amount of labile (between 44% and 58%) and recalcitrant DOC (between 42% and 56%), while C. prolifera community produced mainly recalcitrant DOC (between 64% and 87%). Therefore, this research revealed that temperature is an important factor determining the NCP in benthic communities and the chemical structure and bioavailability of DOC produced by these communities, since both communities tended to produce more humic‐like and less bioavailable DOC with increasing temperature.

Urgently needed transition pathways toward sustainability in agriculture: the case of Persian lime (Citrus latifolia Tanaka) production in Veracruz, Mexico - Susana Isabel Castillo-Martínez; Julio Díaz-José; Otto Raúl Leyva-Ovalle; Emmanuel de Jesús Ramírez-Rivera; Oscar Díaz-José; Joaquín Murguía-González; José Fernando Grass Ramírez; Juan Guillermo Cruz-Castillo (Environment, Development and Sustainability, 2022)

PIMS-TS immunophenotype: description and comparison with healthy children, Kawasaki disease and severe viral and bacterial infections - Alberto García-Salido; Inés Leoz-Gordillo; Anthony González Brabin; María Ángeles García-Teresa; Amelia Martínez-de-Azagra-Garde; María Isabel Iglesias-Bouzas; Marta Cabrero-Hernández; Gema De Lama Caro-Patón; José Luis Unzueta-Roch; Ana Castillo-Robleda; Manuel Ramirez-Orellana; Montserrat Nieto-Moro (Infectious Diseases, 2022)

Timing of Increment Formation in Atlantic Bluefin Tuna (Thunnus thynnus) Otoliths - Enrique Rodriguez-Marin; Dheeraj Busawon; Patricia L. Luque; Isabel Castillo; Nathan Stewart; Kyne Krusic-Golub; Aida Parejo; Alex Hanke (Fishes, 2022)
Controversies remain regarding the periodicity, or seasonality, of otolith growth band formation, which directly influences a correct age determination of Atlantic bluefin tuna using this structure. The aim of this work was to apply marginal increment analysis and marginal edge analysis to determine the timing of band deposition. The index of completion was analyzed using general additive models to evaluate the importance of variables, such as month, age/size, and reader. Results indicate that the opaque band formation begins in June and is completed by the end of November. From the end of the year to the beginning of the following year, there is minimal marginal edge growth as the translucent band begins to form. The translucent zone then reaches a maximum development in May. The results obtained in this study provide evidence that the annulus formation in the otoliths of Atlantic bluefin tuna are completed later in the calendar year than previously thought. This would mean it is necessary to delay the date of the current July 1st adjustment criterion to November 30.

Nonalcoholic Steatohepatitis Modifies Serum Iron-Related Variables in Patients with Morbid Obesity - Anna Hernández-Aguilera; Núria Casacuberta; Helena Castañé; Montserrat Fibla; Salvador Fernández-Arroyo; Isabel Fort-Gallifa; Marta París; Fàtima Sabench; Daniel Del Castillo; Gerard Baiges-Gaya; Elisabet Rodríguez-Tomàs; Teresa Sans; et al. (Biological Trace Element Research, 2021)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Addressing the challenges of climate-driven community-led resettlement and site expansion: knowledge sharing, storytelling, healing, and collaborative coalition building - Julie Maldonado; Itzel Flores Castillo Wang; Fred Eningowuk; Lesley Iaukea; Aranzazu Lascurain; Heather Lazrus; Chief Albert Naquin; JR Naquin; Kukuya Margarita Nogueras-Vidal; Kristina Peterson; Isabel Rivera-Collazo; M. Kalani Souza; et al. (Journal of Environmental Studies and Sciences, 2021)
Presently coastal areas globally are becoming unviable, with people no longer able to maintain livelihoods and settlements due to, for example, increasing floods, storm surges, coastal erosion, and sea level rise, yet there exist significant policy obstacles and practical and regulatory challenges to community-led and community-wide responses. For many receiving support only at the individual level for relocation or other adaptive responses, individual and community harm is perpetuated through the loss of culture and identity incurred through forced assimilation policies. Often, challenges dealt to frontline communities are founded on centuries of injustices. Can these challenges of both norms and policies be addressed? Can we develop socially, culturally, environmentally, and economically just sustainable adaptation processes that supports community responses, maintenance and evolution of traditions, and rejuvenates regenerative life-supporting ecosystems? This article brings together Indigenous community leaders, knowledge-holders, and allied collaborators from Louisiana, Hawai‘i, Alaska, Borikén/Puerto Rico, and the Marshall Islands, to share their stories and lived experiences of the relocation and other adaptive challenges in their homelands and territories, the obstacles posed by the state or regional governments in community adaptation efforts, ideas for transforming the research paradigm from expecting communities to answer scientific questions to having scientists address community priorities, and the healing processes that communities are employing. The contributors are connected through the Rising Voices Center for Indigenous and Earth Sciences, which brings together Indigenous, tribal, and community leaders, atmospheric, social, biological, and ecological scientists, students, educators, and other experts, and facilitates intercultural, relational-based approaches for understanding and adapting to extreme weather and climate events, climate variability, and climate change.

Anti-inflammatory and sedative activities of Peperomia galioides : in vivo studies in mice - Isabel Wilches; Priscila Jiménez-Castillo; Nancy Cuzco; M. Victoria Clos; Francesc Jiménez-Altayó; Eugenia Peñaherrera; Lourdes Jerves-Andrade; Vladimiro Tobar; Yvan Vander Heyden; Fabián Leon-Tamariz; Elisabet Vila (Natural Product Research, 2021)

Streptomyces sp. M54: an actinobacteria associated with a neotropical social wasp with high potential for antibiotic production - Bernal Matarrita-Carranza; Catalina Murillo-Cruz; Roberto Avendaño; María Isabel Ríos; Max Chavarría; María Luisa Gómez-Calvo; Giselle Tamayo-Castillo; Juan J. Araya; Adrián A. Pinto-Tomás (Antonie van Leeuwenhoek, 2021)

Effect of the addition of Enterolobium cyclocarpum pods and Gliricidia sepium forage to Brachiaria brizantha on dry matter degradation, volatile fatty acid concentration, and in vitro methane production - Isabel Cristina Molina-Botero; Johanna Mazabel; Jeyder Arceo-Castillo; José Luis Urrea-Benítez; Leticia Olivera-Castillo; Rolando Barahona-Rosales; Ngonidzashe Chirinda; Juan Ku-Vera; Jacobo Arango (Tropical Animal Health and Production, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Space-temporary variation of the population of long-finned pilot whales (Globicephala melas) in the SE of the Iberian peninsula - Rosa Canales-Cáceres; Francisco Gomariz-Castillo; Francisco Alonso; Isabel Abel; Francisca Giménez-Casalduero (Frontiers in Marine Science, 2019)

Feeding ecology of Mediterranean common dolphins: The importance of mesopelagic fish in the diet of an endangered subpopulation - Joan Giménez; Ana Marçalo; Manuel García‐Polo; Isabel García‐Barón; Juan José Castillo; Carolina Fernández‐Maldonado; Camilo Saavedra; M. Begoña Santos; Renaud de Stephanis (Marine Mammal Science, 2018)
The Mediterranean subpopulation of common dolphin ( Delphinus delphis ) is classified as endangered by the IUCN . Still, information about their diet in the Mediterranean is scarce. Stomach contents of 37 common dolphins stranded in the Alboran Sea and Strait of Gibraltar were analyzed. A total of 13,634 individual prey of 28 different taxa were identified. For fish, Myctophidae was the most important family as indicated by the highest index of relative importance ( IRI = 8,470), followed by the family Sparidae ( IRI = 609). The most important Myctophidae species was Madeira lantern fish ( Ceratoscopelus maderensis ) and for Sparids, the bogue ( Boops boops ). Cephalopods, instead, were found in low quantities only with 31 prey from the Loliginidae, Ommastrephidae, and Sepiolidae families. Overall, our results indicate that common dolphins are mainly piscivorous (99.77% N , 94.59% O , 99.73% W ), feeding mostly on mesopelagic prey. Although common dolphins inhabit mainly coastal waters in the study area, the narrow continental shelf seems to facilitate the availability of Myctophids and other members of the mesopelagic assemblage to dolphins when the assemblage migrates to the surface at night. Our results represent the first attempt at quantifying the diet of this predator in the Alboran Sea and Strait of Gibraltar.

Molecular characterization and clinical interpretation of BRCA1/BRCA2 variants in families from Murcia (south-eastern Spain) with hereditary breast and ovarian cancer: clinical–pathological features in BRCA carriers and non-carriers - Xavier Gabaldó Barrios; Mª Desamparados Sarabia Meseguer; Miguel Marín Vera; Ana Isabel Sánchez Bermúdez; José Antonio Macías Cerrolaza; Pilar Sánchez Henarejos; Marta Zafra Poves; Mª Rosario García Hernández; Encarna Cuevas Tortosa; Ángeles Aliaga Baño; Verónica Castillo Guardiola; Pedro Martínez Hernández; et al. (Familial Cancer, 2017)

On the Role of Mining Exposure in Epigenetic Effects in Parkinson’s Disease - Sebastian Castillo; Patricia Muñoz; Maria Isabel Behrens; Fernando Diaz-Grez; Juan Segura-Aguilar (Neurotoxicity Research, 2017)

Microsatellite records for volume 9, issue 1 - Ana Castillo-Páez; Axayácatl Rocha-Olivares; Celia Isabel Bisbal-Pardo; Dongfa Zhu; Dongmei Zhu; Hajime Itoh; Hiroaki Fukumori; Joichiro Koseki; John Carlos Garza; Jotaro Urabe; Yefeng Lv; Masayuki Maki; et al. (Conservation Genetics Resources, 2017)

BDNF concentrations and daily fluctuations differ among ADHD children and respond differently to methylphenidate with no relationship with depressive symptomatology - Isabel Cubero-Millán; María-José Ruiz-Ramos; Antonio Molina-Carballo; Sylvia Martínez-Serrano; Luisa Fernández-López; Irene Machado-Casas; Pilar Tortosa-Pinto; Aida Ruiz-López; Juan-de-Dios Luna-del-Castillo; José Uberos; Antonio Muñoz-Hoyos (Psychopharmacology, 2017)

Validation of a new catalysed reporter deposition–fluorescence in situ hybridization probe for the accurate quantification of marine B acteroidetes populations - Silvia G. Acinas; Isabel Ferrera; Hugo Sarmento; Cristina Díez‐Vives; Irene Forn; Clara Ruiz‐González; Francisco M. Cornejo‐Castillo; Guillem Salazar; Josep M. Gasol (Environmental Microbiology, 2015)
Summary Catalysed reporter deposition–fluorescence in situ hybridization ( CARD‐FISH ) is a powerful approach to quantify bacterial taxa. I n this study, we compare the performance of the widely used B acteroidetes CF 319 a probe with the new CF 968 probe. In silico analyses and tests with isolates demonstrate that CF 319 a hybridizes with non‐ B acteroidetes sequences from the R hodobacteraceae and A lteromonadaceae families. We test the probes’ accuracy in 37 globally distributed marine samples and over two consecutive years at the B lanes B ay M icrobial O bservatory ( NW M editerranean). We also compared the CARD‐FISH data with the B acteroidetes 16 S rRNA gene sequences retrieved from 27 marine metagenomes from the TARA Oceans expedition. We find no significant differences in abundances between both approaches, although CF 319 a targeted some unspecific sequences and both probes displayed different abundances of specific B acteroidetes phylotypes. Our results demonstrate that quantitative estimations by using both probes are significantly different in certain oceanographic regions ( M editerranean Sea, R ed Sea and A rabian Sea) and that CF 968 shows seasonality within marine B acteroidetes , notably large differences between summer and winter that is overlooked by CF 319 a . We propose CF 968 as an alternative to CF 319 a for targeting the whole B acteroidetes phylum since it has better coverage, greater specificity and overall better quantifies marine B acteroidetes .

Differential responses of two related neurosteroids to methylphenidate based on ADHD subtype and the presence of depressive symptomatology - Antonio Molina-Carballo; Fuensanta Justicia-Martínez; Francisco Moreno-Madrid; Isabel Cubero-Millán; Irene Machado-Casas; Laura Moreno-García; Josefa León; Juan-de-Dios Luna-del-Castillo; José Uberos; Antonio Muñoz-Hoyos (Psychopharmacology, 2014)

Metagenomic 16S rDNA I llumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities - Ramiro Logares; Shinichi Sunagawa; Guillem Salazar; Francisco M. Cornejo‐Castillo; Isabel Ferrera; Hugo Sarmento; Pascal Hingamp; Hiroyuki Ogata; Colomban de Vargas; Gipsi Lima‐Mendez; Jeroen Raes; Julie Poulain; et al. (Environmental Microbiology, 2014)
Summary Sequencing of 16S rDNA polymerase chain reaction ( PCR ) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR . Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes ( mi tag s) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the T ara O ceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for R oche‐454 sequencing using both shotgun ( m454 tag s; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon ( 454 tag s; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mi tag s may provide more realistic estimates of community richness and evenness than amplicon 454 tag s. In addition, mi tag s can capture expected beta diversity patterns. Using mi tag s is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic ( B acteria, A rchaea and E ukarya) and functional information from the same microbial community.

Draft whole genome sequence of the cyanide‐degrading bacterium P seudomonas pseudoalcaligenes CECT 5344 - Víctor M. Luque‐Almagro; Felipe Acera; Ma Isabel Igeño; Daniel Wibberg; Ma Dolores Roldán; Lara P. Sáez; Magdalena Hennig; Alberto Quesada; Ma José Huertas; Jochen Blom; Faustino Merchán; Ma Paz Escribano; et al. (Environmental Microbiology, 2013)
Summary P seudomonas pseudoalcaligenes CECT 5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P . pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other P seudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.

Potato, an experimental and natural host of the crinivirus Tomato chlorosis virus - Isabel M. Fortes; Jesús Navas-Castillo (European Journal of Plant Pathology, 2012)

Gene Expression Analysis during Interaction of Tomato and Related Wild Species with Clavibacter michiganensis subsp. michiganensis - José Pablo Lara-Ávila; María Isabel Isordia-Jasso; Rosalba Castillo-Collazo; June Simpson; Ángel Gabriel Alpuche-Solís (Plant Molecular Biology Reporter, 2012)

Shrub encroachment can reverse desertification in semi‐arid Mediterranean grasslands - Fernando T. Maestre; Matthew A. Bowker; María D. Puche; M. Belén Hinojosa; Isabel Martínez; Pablo García‐Palacios; Andrea P. Castillo; Santiago Soliveres; Arántzazu L. Luzuriaga; Ana M. Sánchez; José A. Carreira; Antonio Gallardo; et al. (Ecology Letters, 2009)
The worldwide phenomenon of shrub encroachment in grass‐dominated dryland ecosystems is commonly associated with desertification. Studies of the purported desertification effects associated with shrub encroachment are often restricted to relatively few study areas, and document a narrow range of possible impacts upon biota and ecosystem processes. We conducted a study in degraded Mediterranean grasslands dominated by Stipa tenacissima to simultaneously evaluate the effects of shrub encroachment on the structure and composition of multiple biotic community components, and on various indicators of ecosystem function. Shrub encroachment enhanced vascular plant richness, biomass of fungi, actinomycetes and other bacteria, and was linked with greater soil fertility and N mineralization rates. While shrub encroachment may be a widespread phenomenon in drylands, an interpretation that this is an expression of desertification is not universal. Our results suggest that shrub establishment may be an important step in the reversal of desertification processes in the Mediterranean region.

Regeneration of different cultivars of common bean (Phaseolus vulgaris L.) via indirect organogenesis - Jesús Arellano; Sara Isabel Fuentes; Patricia Castillo-España; Georgina Hernández (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Physalis ixocarpa and P. peruviana, new natural hosts of Tomato chlorosis virus - Helena P. Trenado; Isabel M. Fortes; Diamantina Louro; Jesús Navas-Castillo (European Journal of Plant Pathology, 2007)

Changes with ageing in several leukocyte functions of male and female rats - Mnica De La Fuente; Isabel Baeza; Noelia Guayerbas; Marta Puerto; Carmen Castillo; Veronica Salazar; Carmen Ariznavarreta; Jesus A. F-tresguerres (Biogerontology, 2004)

In vivo inhibition of nitrogenase by hydroxylamine in Rhodospirillaceae Role of nitric oxide - F. Javier Caballero; M. Isabel Igeo; Rafael Quiles; Francisco Castillo (Archives of Microbiology, 1992)

Regulation of reduced nitrogen assimilation in Rhodobacter capsulatus E1F1 - Francisco Javier Caballero; Isabel Igeo; Jacobo Crdenas; Francisco Castillo (Archives of Microbiology, 1989)